The Role of the Regency Government in Optimizing the Performance of MSMEs and Islamic Financial Institutions in Bangkalan - Mariyatul Kiptiyah; Moh. Ibnu Rusy Ramadhan; M. Syarif Hidayatullah (Managing: Jurnal Bisnis dan Manajemen, 2025)
This study aims to analyze the role of the Bangkalan Regency Government in optimizing the performance of Micro, Small, and Medium Enterprises (MSMEs) and Islamic financial institutions in the region. Given that MSMEs contribute significantly to the local economy, this study explores government policies and programs that support MSME development and how Islamic financial institutions can play a strategic role. The method used in this study is a qualitative approach through data collection through literature studies and documentation studies. The results obtained from the study indicate that government policy support, such as the provision of capital assistance and training, as well as collaboration with Islamic financial institutions, has increased financing accessibility and strengthened the capacity of MSMEs. However, challenges such as lack of financial literacy and limited infrastructure still need to be addressed. This study recommends increasing synergy between the government, MSMEs, and Islamic financial institutions to achieve optimal and sustainable performance in Bangkalan Regency.